Research on Crimp Pitch Measurement for Overhead Transmission Line Based on Image Processing With Composite Algorithm - Junjie Zhang; Huashen Guan; Qiushen Cai; Xiaoguang Zhang; Huitu Shao; Shengguan Qu (Engineering Reports)
ABSTRACT Electric power transmission reliability depends critically on the crimping quality of overhead transmission lines. Poor crimping connections can lead to serious accidents, including wire breakage and dislodgement. Crimping pitch is a key factor for crimping quality, which is used to determine over‐crimping or under‐crimping. Currently, the indentation pitch is manually checked after operation, while the automatic method has not yet been widely studied. This paper proposes an automated crimp pitch measurement system for overhead transmission lines based on image processing with a composite algorithmic approach. First, the indentation enhancement algorithm and indentation segmentation algorithm are used on the captured image to accurately identify the indentation region. Subsequently, the Random Sample Consensus (RANSAC) algorithm utilizes identified edge points to perform robust indentation curve fitting. Finally, the actual crimp pitch is obtained according to the crimp pitch calculation formula. The test results show that the method's measurement accuracy of spacing reaches 3 mm, the maximum relative error is 3.64%, and the standard deviation of repeated measurements is 1.184 mm. The method proposed in this paper can be used for the measurement of crimp pitch, which is characterized by accuracy and efficiency. This approach is particularly suitable for quality control inspections of crimping connections in overhead transmission line systems.